ANALISIS PERSAMAAN SIMULTAN DARI TOBIN’S Q, KEPEMILIKAN MANAJERIAL DAN KEBIJAKAN UTANG - Wahidawati Wahidawati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The purpose of this research to estimates a simultaneous equations model with Tobin’s Q (firm value), managerial ownership and debt policy jointly determined within the system. This research is based on the pre¬vious¬ research by Chen and Steiner (2000), which found that managerial ownership tobe a significant and positive determinant of the level Tobin’s Q. Chen and Steiner (1999) observed evidence of subtituons-monitoring effects between managerial ownership and debt policy.The research is focused on manufacturing companies listed in BEJ for periode 1999-2002.The method of data collection is done by using pooling method and give 151 firm year observation.This research uses a non linear simultaneous equation methodology with use the statistical method two stage least square. The result of research provides empirical evidence : First, that managerial ownership has a non linear relation with Tobin’s Q (we find support for both an alignmenteffect and an entrenchment effectin the relationship between managerial ownership and Tobin’s Q. second, The result supports the argument that managerial ownership helps to resolve the agency conflicts between stock holder and manager. The result also indicate that there is not subtitu¬ta¬bi¬li¬ty between debt and managerial ownership.